2018
DOI: 10.1111/vde.12514
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous prick test irritant threshold concentrations for eight allergens in healthy nonsedated dogs in the USA

Abstract: These results suggest that the pollen allergens evaluated in this study can be used for PT at their undiluted concentration (1:20 w/v) with a reasonable assurance of few false positive reactions in dogs. Dust mites require dilution for testing at the ITC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 11 publications
1
37
0
1
Order By: Relevance
“…In the study by Carnett and Plant performed in dogs, the authors reported the most appropriate concentration to be used when testing for pollen allergens in dogs. The authors reported a 1/20 dilution for this type of allergens, which is consistent with the concentration used in our study (17).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study by Carnett and Plant performed in dogs, the authors reported the most appropriate concentration to be used when testing for pollen allergens in dogs. The authors reported a 1/20 dilution for this type of allergens, which is consistent with the concentration used in our study (17).…”
Section: Discussionsupporting
confidence: 91%
“…The earliest report in the literature on the use of SPT in dogs dates to 1991 (16), where authors found that IDT test reactions were identifiable and that the SPT tests did not give easily interpretable responses. Currently, only the work by Ballauf (16) reported the use of SPT in dogs suffering from dermal or respiratory problems, whereas two other studies reported the results of SPT in non-allergic dogs (17,18). More studies are warranted to evaluate the usefulness of SPT in the causative allergen detection of AD together with the correlation of the serum levels of specific IgE to each allergen tested (19).…”
Section: Introductionmentioning
confidence: 99%
“…95 The PPT is widely used in human allergology to test for allergic rhinitis, eczema, asthma and food allergy. 96,97 In small animal dermatology, very few studies have assessed the usefulness of PPT in dogs 98,99 and cats 93,100 with environmental allergies. In dogs, the first study 99 comparing IDT and PPT showed that IDT was much easier to interpret than PPT, and thus for more than two decades the PPT was abandoned.…”
Section: Intradermal Testingmentioning
confidence: 99%
“…undiluted). 93,98 Once the patient is sedated, the lateral thorax is clipped and the sites for the "pricks" are marked. Then, a drop (0.05 mL) of the allergen (or control) is applied and introduced into the skin via the prick device.…”
Section: Intradermal Testingmentioning
confidence: 99%
See 1 more Smart Citation